Divine Diplomacy: Religious Influence in Global Policymaking - Fitri Pebriani Wahyu; Ahmad Mufarih Hasan Fadly (Religion and Policy Journal, 2023)
Research Problem: This research aims to investigate the complex interactions between religion and global policymaking and their impact on international relations.